EFEKTIFITAS PROGRAM SATU RUMAH SATU JUMANTIK DALAM PENGENDALIAN DEMAM BERDARAH DENGUE (DBD) DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Viranti Oktiodirman; Zaili Rusli (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The One House One Jumantik (1R1J) program is community participation and empowerment by involving every family in the inspection, monitoring and eradication of mosquito larvae to control Dengue Hemorrhagic Fever (DHF) through the 3M Plus PSN culture. The purpose of the study was to look at the effectiveness of the One House One Jumantik Program in controlling dengue fever in Tenayan Raya District, Pekanbaru City and the factors inhibiting the effectiveness of the program. In this study using descriptive qualitative research methods, data obtained from the interview, observation and documentation process were collected and then analyzed based on the findings of the research problem, and used the theory of program effectiveness according to Muasaroh which consisted of several indicators that became a measure of program effectiveness, namely aspects of tasks and activities. functions, aspects of plans and programs, aspects of provisions and regulations, and aspects of goals and ideal conditions. The results of this study indicate that the One House One Jumantik program in Tenayan Raya District, Pekanbaru City is not running optimally or can be said to be ineffective, because the program does not run according to the Standard Operating Procedures (SOP) that have been set. The inhibiting factors are all aspects of measuring the success of problematic programs, starting from aspects of tasks and functions, aspects of plans and programs, aspects of provisions and regulations, and aspects of goals and ideal conditions. Researchers suggest that the process of forming program plans needs to be maximized and conditioned in various regions and the need to provide knowledge through socialization to the community so that the program can run optimally and program objectives can be realized.